Turnover is Coming: Strategies to Prepare for Impending Retirements. Issue 4 (18th May 2020) - Corbin, Jennifer L.
Abstract: Libraries have long been concerned about aging library professionals. Libraries that have not experienced high rates of retirement and turnover may not be prepared to bring on new personnel using a supportive approach. Onboarding librarians and library staff can increase employee retention. This includes strategies for librarians who are coping with managing high turnover, including learning about the organization's recruitment procedures, creating an onboarding plan that includes training and documentation, and taking care of oneself.